COTTON PRODUCTION: EFFECT OF APPLICATION RATES AND TIMING OF NEW MICROELEMENT FERTILIZERS ON COTTON GROWTH AND DEVELOPMENT - Gulnora Alijonovna Abdullayeva; Qaxramonjon Anvarjonovich Davronov; Umida Qurbonali qizi Tillavoldiyeva (Web of Journals Publishing, 2025)
The principles of soil science and agrochemistry are used to maintain and increase soil fertility and to provide cotton with mineral nutrition on a scientific basis. The main problems in cotton growing are: ecological problems and environmental protection, soil fertility, wind and water erosion, labor productivity and the efficiency of all agrotechnical measures in the field; increasing cotton yield; improving product quality are among the urgent issues.
Keywords: Cotton growing, micronutrients, microorganisms, cotton, physiologically active substances, combing, flowering. phenological observation, soil fertility, boll, plant height.